Menggali Konsep Rekonsiliasi dalam Teologi Kristen sebagai Dasar Alternatif Penyelesaian Perkara Pidana yang Melibatkan Kelompok LGBT - Majesty, Gilbert Timothy; Rani Sibarani (Sukacita : Jurnal Pendidikan Iman Kristen, 2026)
This study aims to explore the concept of reconciliation in Christian theology as a philosophical foundation for an alternative criminal justice model involving the LGBT community. The retributive criminal law approach is often considered ineffective in addressing the complexities of legal, social, and religious conflicts related to religious sexual minorities. Using a qualitative method and a constructivist approach, this study analyzes the meaning of reconciliation through sacred texts, doctrine, and interviews with theologians, legal practitioners, and the Christian LGBT community. This approach reveals the subjective understanding of the actors regarding reconciliation and justice. The findings show that the core of reconciliation theology is the restoration of relationships, recognition, and transformation, which can form an ethical framework for the restorative justice model. This model offers a holistic solution, not only addressing legal consequences but also restoring social harmony by respecting individuals' dual identities. The article concludes that the integration of theological insights can lead to a more inclusive and transformative criminal justice paradigm for the LGBT community, resulting in a more humane and just resolution.